2019
DOI: 10.1177/1010539519872061
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nutritional Status in Sri Lankan Children: Validity of Current Anthropometry Cutoffs?

Abstract: Despite socioeconomic improvement, undernutrition rates stagnate in Sri Lanka, while a slow rise in obesity and noncommunicable diseases (NCD) is seen. Inability to improve undernutrition and detection of NCD could be due to overdiagnosing stunting/wasting and underdiagnosing overweight/obesity. Obesity, being a risk factor for NCDs, needs correct tools for early diagnosis. Although body mass index (BMI) is a commonly used surrogate index, the validity of universal cutoffs is questioned. Evidence shows that bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
(46 reference statements)
1
8
0
Order By: Relevance
“…It's agreed with one of the study carried out among students aged 5-15 years studying in Negombo schools where prevalence of obesity identified by body fat content was high and reported that as validity of internationally developed anthropometric cut-offs in South Asian children is unsatisfactory; locally regionally developed anthropometric tools should be used for screening of obesity (15). Further, South Asian countries face a double burden of malnutrition characterized by high prevalence of underweight, overweight, and obesity.…”
Section: Discussionsupporting
confidence: 64%
“…It's agreed with one of the study carried out among students aged 5-15 years studying in Negombo schools where prevalence of obesity identified by body fat content was high and reported that as validity of internationally developed anthropometric cut-offs in South Asian children is unsatisfactory; locally regionally developed anthropometric tools should be used for screening of obesity (15). Further, South Asian countries face a double burden of malnutrition characterized by high prevalence of underweight, overweight, and obesity.…”
Section: Discussionsupporting
confidence: 64%
“…All children identified as having obesity (BMI‐SDS ≥ +2SD according to WHO, 2007) in a cross‐sectional survey carried out in Sri Lankan schools 27 were invited to the Diabetes Screening and Vocational Training Centre of the Lions Club of Negombo Host for further examination and possible treatment. Children with chronic diseases, secondary causes for obesity or on long term medication were excluded according to judgment of the clinical examiner.…”
Section: Methodsmentioning
confidence: 99%
“…Data from Colombo municipal area showed overweight and obesity to be about 14% among 8- to 12-year-old school children [ 3 ] and in Colombo district about 13% among 5- to 15-year-old children [ 4 ]. In the Negombo education zone, overnutrition was shown to vary between 10 and 18% across 5–15 year age group with the prevalence increasing with age [ 5 ].…”
Section: Introductionmentioning
confidence: 99%